Crustal Structures, Geothermal Sources and Pathways Beneath Northern Thailand Revealed by Local Earthquake Tomography - Kasemsak Saetang (Science Faculty of Chiang Mai University, 2019)
We present the first seismic velocity models beneath the northern part of Thailand by using local earthquake tomography method. The study area is located in a seismic active area, with earthquakes recorded by the Seismological Bureau (SB) under the Thai Meteorological Department, as well as the United States Geological Survey (USGS); with data available by Incorporated Research Institutions for Seismology (IRIS). Vp and Vs models were created for an advanced understanding of the characteristics of the crust and geothermal sources by using earthquake waveforms acquired from eight permanent stations which were deployed by the SB. Tomographic inversions were presented in a 10 km horizontal and 5 km vertical grid spacing covering an area of 300´300 km. The first arrival time of P and S were manually picked in a SeisGram2k Version 7.0 software after noise filtering for tomographic inversions. The tomographic inversion was done by the LOTOS-12 code for creating 3D velocity models. Velocity models are presented in horizontal sections and vertical profiles covered by seismic ray paths for interpretations. Results are compared with geological information and previous works. Low velocity anomalies in shallow depths could directly relate to basin locations. We interpret the deeper parts of low anomalies beneath hot springs as geothermal sources caused by hotter rock material. High Vp/Vs ratios expected to be hotter materials with higher fluid content appear below mountain ranges. The Moho depth at 35 km beneath the study area was assumed using refracted waves and also coincides with previous works.